Cochlear implants and bacterial meningitis: a speech recognition study in paired samples - Brito,Rubens de (2013)
INTRODUCTION: Cochlear implants may guarantee sound perception and the ability to detect speech at a close-to-normal hearing intensity; however, differences have been observed among implantees in terms of performance on discrimination tests and speech recognition. OBJECTIVE: To identify whether patients with post-meningitis deafness perform similarly to patients with hearing loss due to other causes. METHOD: A retrospective clinical study involving post-lingual patients who had been using Nucleus-22 or Nucleus-24 cochlear implants for at least 1 year. These patients were matched with respect to age (± 2 years), time since the onset of deafness (± 1 year), and the duration of implant use with implant users who had hearing loss due to other causes. Speech perception was assessed using the Portuguese version of the Latin-American Protocol for the Evaluation of Cochlear Implants. RESULTS: The sample consisted of 52 individuals (26 in each of the 2 groups). The post-meningitic group had a median of 18.5 active electrodes. The group with hearing loss due to other causes had a median of 21, but no significant statistical difference was observed (p = 0.07). The results of closed- and open-set speech recognition tests showed great variability in speech recognition between the studied groups. These differences were more pronounced for the most difficult listening tasks, such as the medial consonant task (in the vowel-consonant-vowel format). CONCLUSION: Cochlear implant recipients with hearing loss due to bacterial meningitis, who had been using the device for 1 year performed more poorly on closed- and open-set speech recognition tests than did implant recipients with hearing loss due to other causes.